Studying the Properties of Water Activated by Hybrid Plasma for Biological and Medical Applications - Naeim, Farah A.; Humud, Hammad R. (Iraqi Journal of Science, 2025)
This work investigates the chemical and physical properties of water activated by Hybrid plasma, using argon gas. Two ways were used to activate the water: the first one was done by mixing the argon gas and air at atmospheric pressure at two flow rates of 0.7 and 1.0 L/min, and the second, used only atmospheric air. To study the physical and chemical properties of water, 10 cm3 of distilled water was placed in a container made of glass in the form of a dish with a diameter of 5 cm and 1 cm depth; an AC sinewave voltage of 12 kV, a frequency of 20 kHz, and power of 36 watts was used; the exposure time ranged from 1-30 minutes. The generated RONS (oxygen nitrogen reactive species) were quantified utilizing tools designed specifically for this objective. The results showed that NO2, NO3 and H2O2 concentrations increased with the exposure time but they decreased with the increases the flow rate. The water pH in both methods decreased with the exposure time until it reached 2.3; the water temperature increased reaching 51.7°C with the first method and 50.6°C with the second method. The pH increased with the storage time, and the plasma activated water (PAW) reached the natural pH value of 7 after 24 hours of storage. From these findings, it can be concluded that Hybrid plasma discharge can produce RONS that may be applied in biological applications.